Chronic Pain: Lost Inhibition? - Henderson, Luke A.; Peck, Chris C.; Petersen, Esben T.; Rae, Caroline D.; Youssef, Andrew M.; Reeves, Jenna M.; Wilcox, Sophie L.; Akhter, Rahena; Murray, Greg M.; Gustin, Sylvia M. (The Journal of neuroscience, 2013)
Human brain imaging has revealed that acute pain results from activation of a network of brain regions, including the somatosensory, insular, prefrontal, and cingulate cortices. In contrast, many investigations report little or no alteration in brain activity associated with chronic pain, particularly neuropathic pain. It has been hypothesized that neuropathic pain results from misinterpretation of thalamocortical activity, and recent evidence has revealed altered thalamocortical rhythm in individuals with neuropathic pain. Indeed, it was suggested nearly four decades ago that neuropathic pain may be maintained by a discrete central generator, possibly within the thalamus. In this investigation, we used multiple brain imaging techniques to explore central changes in subjects with neuropathic pain of the trigeminal nerve resulting in most cases (20 of 23) from a surgical event. Individuals with chronic neuropathic pain displayed significant somatosensory thalamus volume loss (voxel-based morphometry) which was associated with decreased thalamic reticular nucleus and primary somatosensory cortex activity (quantitative arterial spin labeling). Furthermore, thalamic inhibitory neurotransmitter content was significantly reduced (magnetic resonance spectroscopy), which was significantly correlated to the degree of functional connectivity between the somatosensory thalamus and cortical regions including the primary and secondary somatosensory cortices, anterior insula, and cerebellar cortex. These data suggest that chronic neuropathic pain is associated with altered thalamic anatomy and activity, which may result in disturbed thalamocortical circuits. This disturbed thalamocortical activity may result in the constant perception of pain.